Outlawed Honor: a Thesis on Dueling in South Carolina - Withers, David (My University, 2013)
This essay will analyze the honor culture of South Carolina to discover why it is that after the state outlawed dueling in any form, men and occasionally women both continued to fight and die over dozens of personal issues. The focus will take place between the years of 1812, when South Carolina first outlawed dueling, and 1865, when the practice fell so far out of favor with the public that it began to cease altogether. To understand this, two things must be discussed before all others: what a duel is and what constituted as honor. A duel is an occasion in which two parties of equal social stature--one the offender, the other the offended--agree to meet in a private place with a small group of witnesses for the purpose of satisfying the offended person's injured honor. Honor is a person?s reputation for being virtuous, strong, and brave; it was often perceived as a gentleman's most precious possession and thus had to be defended even at the risk of one's life. This mentality was the primary cause for wealthy men and women to continue to hold duels despite the fear of legal persecution following the 1812 legislation, all the way to 1865, when it at last began to die out as a practice following the Civil War.
Keywords: South Carolina--Social life and customs--19th century; Honor--South Carolina--History; Honor--Social aspects; Dueling--South Carolina--History--19th century